The question of gender and the culture of Arab feminist creativity by Miaa Abbas Emara as a model - Rasid, . ansam Muhammad (Al-Adab Journal, 2015)
Divided we discussed the question of gender on two complementary moving the first of them to read critical discourse feminist and accountability concepts of the major private gender and follow the development of this term and the role of feminist criticism in establishing the identity of creative for women and writing a man in a great desire to smash the patriarchy dominating all aspects of life including movement and creativity of writing. And wants our search in the segment complementary to dismantle what gender over the creative experience of arab and chose the experience of the poet Iraqi lemeea abbas amara poet pilot did not take her experience creative at large share an analytical and critical suitable for decades of creativity one who wrote about lemeea few does not meet maturely produced poetry and try to respond to our vision and our analysis for, inter alia, that itreminded her of a mature hair line pen